The Relationship Between Organizational Culture and Work Environment on Employee Performance at the Bogor City Regional General Hospital - Abdurachman, Gini Gantini; Agung, Syahrum; Kusuma, Anuraga (INOVATOR, 2024)
This research aims to determine the relationship between organizational culture and the work environment on employee performance. This research was carried out by distributing questionnaires to 93 employees at the Bogor City Regional General Hospital, processed using the SPSS 25 application with the Spearman rank analysis method showing that the relationship between the two variables, namely organizational culture and employee performance, has a relationship that destroys the numbers with a significance of 0.001 which is less. of 0.05 To see the correlation between the two variables, look at the number 0.696 which means "strong relationship". It is known that the relationship between the two variables, namely organizational culture and employee performance, has a bad relationship with a significance figure of 0.001 which is less than 0.05 with the number of samples (N) used being 93 respondents. To see the correlation between the two variables, look at the number 0.382 which means "sufficient relationship", so the correlation between the two variables is significant. In the hypothesis test, the product moment correlation r calculated>r table with 0.734>0.2039 means that the relationship between organizational culture and employee performance has a significant and positive relationship. Meanwhile, the results of the correlation hypothesis test produce rcount>r table with 0.441>0.2039, meaning that the relationship between the work environment and employee performance has a significant and positive relationship.